THE GRUNTS (FAMILY HAEMULIDAE) OF THE SPERMONDE ARCHIPELAGO, SOUTH SULAWESI - Andi Iqbal Burhanuddin; Yukio Iwatsuki (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Fish diversity monitoring could be utilized as a basis for formulating management regulation of the fisheries resources. This study was conducted to describe the grunt of the family Haemulidae from the Spermonde Archipelago, South Sulawesi. Specimens were collected in Rajawali and Paotere Fish Landing Port Makassar, South Sulawesi from August 2003 to November 2010. The results showed that there were thirteen species representing three genera of family Haemulidae inhabiting the area were examined and identified: Diagramma pictum (Thunberg, 1792), Plectorhinchus albovittatus (Rüppell, 1838), Plectorhinchus chaetodonoides Lacepède, 1801, Plectorhinchus chrysotaenia (Bleeker, 1855), Plectorhinchus flavomaculatus (Cuvier in Cuvier and Valenciennes, 1830), Plectorhinchus gibbosus Lacepède, 1802, Plectorhinchus lessonii (Cuvier in Cuvier and Valenciennes, 1830), Plectorhinchus lineatus (Linnaeus, 1758), Plectorhinchus picus (Cuvier in Cuvier and Valenciennes, 1830), Plectorhinchus polytaenia (Bleeker, 1852), Plectorhinchus vittatus (Linnaeus, 1758), Pomadasys argenteus (Forsskål, 1775), Pomadasys maculatus (Bloch, 1793). The local name available of each species was given.Keywords: grunt, haemulidae, spermonde, south Sulawesi